WHEN THE OFFICE NEVER SLEEPS: EMPLOYEE PERFORMANCE IN LEGAL SERVICE FIRMS THROUGH A PLS-SEM LENS - Julian Adam; Sumartik Sumartik; Kumara Adji Kusuma; Dyah Atia Mayang Fa'una; Ananda Ratih Ayu Kumalasari (Antis Publisher, 2026)
Objective: This study analyzes and examines the effect of work-life balance, organizational support, and self-efficacy on employee performance at PT Quanta Sinergi Indonesia. Method: An explanatory quantitative approach with an associative design was used. Data were collected through an online questionnaire distributed to all 56 employees of PT Quanta Sinergi Indonesia using a total sampling technique, and analyzed with SmartPLS version 3.0 through outer model testing, inner model testing (R-square, F-square, and path coefficient), and hypothesis testing using bootstrapping. Results: Work-life balance, organizational support, and self-efficacy each have a positive and significant partial effect on employee performance, and the three variables simultaneously have a positive and significant effect on employee performance. Novelty: This study is the first to simultaneously examine work-life balance, organizational support, and self-efficacy on employee performance within the specific context of a legal service firm, an organizational setting not previously combined in prior research.